Post-marketing safety concerns with pirfenidone and nintedanib: an analysis of individual case safety reports from the FDA adverse event reporting system database and the Japanese adverse drug event report databases - Tao Wang; Zhiwei Cui; Yingyong Ou; Siyu Lou; Huayou Chen; Chengyu Zhu; Linmei Zhou; Fan Zou (Frontiers in Pharmacology)
IntroductionTo date, only two drugs, pirfenidone and nintedanib, are approved for the treatment of patients with idiopathic pulmonary fibrosis (IPF). In addition, very few studies have reported on the safety profile of either drug in large populations. This study aims to identify and compare adverse drug events (ADEs) associated with pirfenidone and nintedanib in real-world settings by analyzing data from the US Food and Drug Administration Adverse Event Reporting System (FAERS). In addition, we utilized data from the Japanese Adverse Drug Event Report (JADER) database for external validation.MethodsThe ADE reports on both drugs from 2014 Q3 to 2024 Q2 in FAERS and from 2008 Q1 to 2024 Q1 in JADER were collected. After deduplication, Bayesian and non-Bayesian methods for disproportionality analysis, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multiple Gamma Poisson Shrinkers (MGPS), were used for signal detection. Additionally, time to onset (TTO) analysis were performed.ResultsIn total, 35,804 and 20,486 ADE reports were identified from the FAERS database for pirfenidone and nintedanib, respectively. At the system organ class (SOC) level, both drugs have a positive signal value for “gastrointestinal disorders,” “respiratory, thoracic, and mediastinal disorders,” and “metabolism and nutrition disorders.” Other positive signals for pirfenidone include “general disorders and administration site conditions,” and “skin and subcutaneous tissue disorders,” while for nintedanib, they were “investigations,” “infections and infestations,” and “hepatobiliary disorders.” Some positive signals were consistent with the drug labels, including nausea, decreased appetite, and weight decreased identified in pirfenidone, as well as diarrhea, decreased appetite, abdominal pain upper, and epistaxis identified in nintedanib. We also identified unexpected signals not listed on the drug label, such as decreased gastric pH, and pneumothorax for pirfenidone, and constipation, flatulence for nintedanib. The median onset time for ADEs was 146 days for pirfenidone and 45 days for nintedanib, respectively. Although the two antifibrotics differed in the proportion of periods in which the ADEs occurred, these ADEs were likely to continue even after a year of treatment. In the external validation of JADER, the number of reports for pirfenidone and nintedanib were 265, and 1,327, respectively. The disproportionality analysis at the SOC and preferred term (PT) levels supports the FAERS results.ConclusionThis study systematically investigates and compares the ADEs and their onset times at the SOC and specific PT levels for pirfenidone and nintedanib. Our results provide valuable pharmacological insights for the similarities and differences between the safety profiles of the two drugs and highlight the importance of monitoring and managing the toxicity profile associated with antifibrotic drugs.